A Wavelet Coder for Masked Images - Simard, Patrice; Malvar, Henrique S. (IEEE Data Compression Conference, 2001)
This paper presents an algorithm for the compression of images that have “don’t care” regions within them. Such regions are specified by an additional binary image, the mask, which we assume is available at both the coder and the encoder (it is transmitted separately and without loss). Unlike previous approaches, which typically fill in the masked pixels with values geared toward good compression of the image, we use a special wavelet transform which is a function of the mask, but which can be computed efficiently. We compare our method with the previous approaches by measuring the compression for a given PSNR on the valid pixels. Our algorithm is both faster and yields compression improvements of up to 18% over the current state-of-the-art coders.